(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
The main objective of the current research is to know the validity of the procedures adopted in the selection of sample unit of different types: whether random samples or non-random samples in social field research Completed (doctoral theses) between 1992- 2012. An appropriate methodology was adopted for the research objective, represented by the descriptive analytical approach, the two methods of content analysis And the social survey using the sample method, and the content analysis form as a basic tool for data collection. The original research community consisted of all doctoral theses in Graduate Studies Library at Damascus University - Faculty of Arts and Human Sciences - Department of Sociology between the years 1992-2012, amounting to 60 doctoral theses. The purposive method was adopted in selecting a sample of doctoral dissertations that met the condition of relying on the sample in the study. The volume reached (45) doctoral dissertations. Based on the statistical analysis of the data that was conducted through the statistical program (SPSS) using percentages, a number of results were reached indicating that the largest percentage of doctoral dissertations completed between the years 1992-2012 were field-based and were supervised by one supervisor, and the students who prepared them were male. It also included the title of the research, the questions, the human field, as well as the hypotheses and the sample unit. The results indicated that the majority of these theses were based in the study on random samples, but without specifying the method adopted for drawing sample members, in addition to adopting the percentage criterion in determining the size of random samples. The results also showed that the largest percentage of doctoral dissertations that used non-random samples in the study adopted the purposive method in selecting sample members, but the criterion adopted in determining the size of non-random samples was not clear.